PENGARUH EKSTRAK SEGAR DAUN ROSELA (Hibiscus sabdariffa L.) TERHADAP JUMLAH ERITROSIT DAN KADAR HEMOGLOBIN MENCIT JANTAN (Mus musculus L.) ANEMIA STRAIN DDW MELALUI INDUKSI NATRIUM NITRIT (NaNO2) - Asmitra Sembiring; Masitta Tanjung; Emita Sabri (Saintia Biologi, 2013)
The purpose of this research is to investigate the effect of fresh leave extract of rosela (Hibiscus sabdariffa L.) on erythrocyte and haemoglobin concentration in anemia male mice (Mus musculus L.) DDW strain induced by sodium nitrite. Completely randomized design (CRD) was used in this experiment, consisting of 5 groups. The first two groups is control induced by NaNO2 for 18 days and the second group is induced by NaNO2 for 18 days and then distilled water for 14 days, and three groups of teratment. The treatment group, divided into three classes of concentration such as; 14 mg/ml (P1), 28 mg/ml (P2) and 42 mg/ml (P3). The treatment group induced by NaNO2 first for 18 days and then healing process by extract of rosela leaves for 14 days. Each class consisted of six experiments animals. The extract was given orally     0.3 ml/day.  The results indicate that leave extract affect on increasing of erythrocytes and hemoglobin concentration that have a significantly different (p<0.05) between control and  treatments.   Keyword: anemic, erythrocytes, haemoglobin, rosela leaves.